A Study to Assess the Effectiveness of Cold Pack Application on Episodic Pain Among Patients with Migraine in Selected Community Areas - K Abinaya; Sharumathi (Wolters Kluwer Medknow Publications, 2024)
Introduction: A migraine is typically described as a sick headache, since the patient apart from the headache feels very sick. Migraine is a genetic neurological disease, characterized by episodes often called Migraine attacks. Objectives: To assess the effectiveness of cold pack application on episodic pain among patients with migraine. To associate the posttest level of episodic pain among patients with migraine with selected demographic variables. Materials and Methods: A quasi experimental group pretest and posttest research design with a purposive sampling technique. The sample size of the study consists of 60 patients with migraine headaches. Results and Discussion: Demographic variables education (χ2 = 16.113, p=0.013) and residence (χ2=7.329, p=0.026) had shown statistically significant association with post test level of episodic pain among patients with migraine at post test level of episodic pain among patients with migraine. Conclusion: This study concluded Cold Pack Application may reduce the level of episodic pain among patients with migraine.